COVID-19 Vaccines and Related Adverse Effects among Health Sciences and Non-Health Sciences Students from Two Large Public Universities in Thailand - Khawcharoenporn, Thana; Jongmekwamsuk, Kanathip; Hanvivattanakul, Sirashat; Vanichanan, Jakaphat (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Existing data on vaccine regimensreceived by university students and related adverse effects (AEs) are limited. Objectives: To assess types and AEs of COVID-19 vaccines received by Thai university students. Methods: An online survey study was conducted among students from 12 Health Sciences faculties (HS), and from 16 non-Health Sciences faculties (NHS) of two universities from October 2021 to January 2022. Results: There were 1,439 participating students; 522 (36%) were HS and 917 (64%) were NHS. The types of the first-dose vaccine received were inactivated (49%), viral vector (VV; 46%), and mRNA (5%), while the types of the second-dose vaccine received were VV (53%), inactivated (40%) and mRNA (7%). For the first-dose vaccines, the most common AEs of inactivated, VV, and mRNA vaccines were muscle pain (47%, 82%, and 58%, respectively). For the second-dose vaccines, the most common AEs were cough (47%) for inactivated vaccines and muscle pain (49% for VV and 56% for mRNA vaccines). VV vaccines were more likely to cause fever, muscle pain, diarrhea, headache, and rashes than the others. The mRNA vaccines caused injection site pain more than inactivated vaccines. The majority of AEs occurred at 24 - 48 hours after vaccination (68%) were more severe with the first dose compared with the second dose and resolved spontaneously without any treatment at a hospital. Conclusions: The AEs experienced by the students were various according to the types and number of dose of COVID-19 vaccines. The AEs were mostly non-severe and occurred less for the second dose compared with the first dose.